Facial Massage Training to Improve Skills Facial Care for Mothers - Ihsani, Ade Novi Nurul; Apriyani, Delta; Maghfiroh, Anik; Handayani, Paramita; Suryani, Parsih Wulan; Syafira, Mauliana (Jurnal Abdimas, 2023)
Beauty is synonymous with personal appearance and is a valuable asset for everyone woman. Facial care for every woman is an almost daily activity done. Daily facial care activities through facial massage aim to slow down process aging on skin face. Crena beauty a woman often identified with healthy, firm skin, free from skin disorders, and no visible aging on the skin face. However, with a busy routine and not accompanied by a good lifestyle, so beauty skin will disturbed Which cause beauty skin neglected. Based on observation beginning Which done on moms in the sub-district hang on subdistrict Gunungpati Semarang about knowledge maintenance skin face with massage face very need knowledge And Skills Because Not yet Once get training about matter the. Objective from devotion This is For give Facial massage knowledge and training to improve facial massage skills for mothers mothers in Ngijo sub-district, Gunungpati District, Semarang so that mothers will have facial massage skills that can be done independently in everyday life. The methods used in this service include 1). Methods of socialization / counseling / awareness, 2). Design method wake up and 3). Evaluation method.